Foley Catheter-Assisted Evacuation of Clot Versus Conventional Craniotomy for Spontaneous Supratentorial Intracerebral Haemorrhage: A Single‑Centre Observational Study - Arumugam, Ananda; Vinayaga, Sakti; Cheah, Pike See; Abdelwahab, Emad Mohamad Nafie (Malaysian Journal of Medical Sciences, 2026)
Background: Minimally invasive surgery (MIS) is increasingly recommended for spontaneous intracerebral haemorrhage (ICH). This study aimed to compare outcomes between patients undergoing Foley catheter-assisted MIS and those treated by conventional craniotomy in a real-world clinical setting.Methods: A single-centre, dual-cohort observational study was conducted. A prospective cohort of consecutive patients (n = 35) who underwent Foley catheter-assisted evacuation was compared with a retrospective historical cohort (n = 35) treated with conventional craniotomy. Eligible patients were adults (18 to 75 years old) with supratentorial ICH volumes ≥ 30 mL and an admission Glasgow Coma Scale (GCS) score of 6–12. Primary outcomes included intraoperative blood loss, surgery duration, and the Glasgow Outcome Scale (GOS) score at 3 months. Secondary outcomes encompassed seizure incidence, rebleeding rates, and Mini-Mental State Examination (MMSE) scores at 1 month postoperatively.Results: Compared with the conventional craniotomy cohort, the Foley catheter cohort was associated with significantly lower intraoperative blood loss (120 ± 30 mL vs. 210 ± 45 mL, P = 0.042), a shorter surgery duration (150 ± 25 min vs. 195 ± 35 min, P = 0.001), and a better GOS score at 3 months (4.1 ± 0.8 vs. 2.9 ± 0.6, P < 0.001). The incidence of postoperative seizures was also lower in the Foley catheter group (5.7% vs. 25.7%, P = 0.021). Rebleeding rates did not differ significantly between the cohorts (11.4% vs. 20.0%, P = 0.324). The MMSE scores at 1 month were higher in the Foley catheter cohort (P < 0.001).Conclusion: In this observational cohort study, Foley catheter-assisted evacuation was associated with reduced operative time, less intraoperative blood loss, a lower incidence of seizures, and better early functional and cognitive outcomes compared with conventional craniotomy. These findings support the potential utility of this technique and warrant further investigation in larger, prospective studies to establish causal efficacy.